A longitudinal experimental analysis on the interaction between a team reflexivity intervention and leadership style - Uitdewilligen, S.; Santos, C. M.; Passos, A. M.; Schippers, M. (11th INGroup Annual Conference, 2016)
This study analyzes the interaction effect between team reflexivity and leadership style (empowering vs. directive) on performance development. Eighty teams participated in an emergency management simulation. The results suggest that the effect of reflexivity on performance is higher in teams with directive leadership than in teams with empowering leadership.